2018
DOI: 10.7717/peerj.5348
|View full text |Cite
|
Sign up to set email alerts
|

Captive gibbons (Hylobatidae) use different referential cues in an object-choice task: insights into lesser ape cognition and manual laterality

Abstract: BackgroundUtilization of visual referential cues by non-human primates is a subject of constant scientific interest. However, only few primate species, mostly great apes, have been studied thoroughly in that regard, rendering the understanding of phylogenetic influences on the underlying cognitive patterns difficult.MethodsWe tested six species of captive gibbons in an object-choice task (n = 11) for their ability to interpret two different pointing gestures, a combination of body orientation and gaze directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…So far, most information on gaze and glance cue understanding in apes derive from studies in which human experimenters signal to an ape subject in a captive setting 3 , 14 , 21 , 22 . It is important to note that responsiveness to human eye orientation by habituated animals does not equate with the usage of glance cues among conspecifics, as for instance the successful exploitation of human glances by Californian sea lions ( Zalophus californianus ) demonstrates 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, most information on gaze and glance cue understanding in apes derive from studies in which human experimenters signal to an ape subject in a captive setting 3 , 14 , 21 , 22 . It is important to note that responsiveness to human eye orientation by habituated animals does not equate with the usage of glance cues among conspecifics, as for instance the successful exploitation of human glances by Californian sea lions ( Zalophus californianus ) demonstrates 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite their phylogenetic position and resulting relevance to understand the evolution of hominoid cognitive traits, gibbons are widely ignored in primate behavioral research (excluding acoustic communication), so that little is known about their socio-cognitive traits 19 , 20 . However, there currently is consensus that glancing does not carry noteworthy communicative value to them 21 , 22 . In line with this, gibbon gaze following is less sophisticated than in their large-bodied relatives.…”
Section: Introductionmentioning
confidence: 99%
“…So far, most information on gaze and glance cue understanding in apes derive from studies in which human experimenters signal to an ape subject in a captive setting (Barth et al, 2005;Tomasello et al, 2007;Caspar et al, 2018;Sanchez-Amaro et al, 2020). It is important to note that responsiveness to human eye orientation by habituated animals does not equate with the usage of glance cues among conspecifics, as for instance the successful exploitation of human glances by Californian sea lions (Zalophus californianus) demonstrates (Arkwright et al, 2016).…”
Section: Is Ocular Pigmentation Linked To Specific Sociocognitive Tramentioning
confidence: 99%
“…Despite their phylogenetic position and resulting relevance to understand the evolution of hominoid cognitive traits, gibbons are widely ignored in primate behavioral research (excluding acoustic communication), so that little is known about their sociocognitive traits (Butler & Suddendorf, 2014;ManyPrimates et al, 2019). However, there currently is consensus that glancing does not carry noteworthy communicative value to them (Caspar et al, 2018;Sanchez-Amaro et al, 2020). In line with this, gibbon gaze following is less sophisticated than in their large-bodied relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the lack of studies on gibbons' socio-cognitive abilities in relation to other primate species 22 , researchers have made signi cant advancements on this area. For instance, it has been investigated whether gibbons recognize themselves in the mirror (see 25 for review) or whether they are able to follow others gaze to discover an unseen object [38][39][40][41][42] . In the case of gaze-following studies, researchers have found that gibbons are able to shift their gaze in response to a previous experimenter gaze shift but it remains unclear whether gibbons are taking the perspective of the experimenter into account, including her mental states.…”
Section: Introductionmentioning
confidence: 99%